Pengaruh Idealisme, Relativisme, Gender dan Tingkat Pengetahuan terhadap Persepsi Mahasiswa Akuntansi atas Perilaku Tidak Etis Akuntan - Efran Efran; Ethika Ethika (Jurnal Kajian Akuntansi dan Auditing, 2020)
This study aims to prove the influence of idealism, relativism, gender and level of knowledge on accounting students perceptions of accountant's unethical behavior. Before the data processing stage is carried out the data collection process is first carried out, in this study the sample is the accounting student at Bung Hatta University who has conducted lectures from the fifth semester onwards. The sampling process is done by purposive sampling method. The data used are primary, which is obtained through questionnaires. In this study, the independent variable consists of idealism, relevance, gender and level of knowledge while the dependent variable is the accounting student's perception of unethical behavior. To test the hypothesis used multiple regression with the help of the SPSS program. Based on the test results it can be concluded that idealism, relevatism, gender, and level of knowledge do not significantly influence the perception of accounting students of unethical behavior in the University of Bung Hatta University.